2018
DOI: 10.1101/441923
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The ULK1-FBXW5-SEC23B nexus controls autophagy

Abstract: In response to nutrient deprivation, the cell needs to mobilize an extensive amount of membrane to form and grow the autophagosome, allowing the progression of autophagy.By providing membranes and a source for LC3 lipidation, COPII (Coat Protein Complex II) localizes to the endoplasmic reticulum (ER)-Golgi intermediate compartment (ERGIC) and promotes autophagosome biogenesis. However, the molecular mechanisms that, in response to starvation, divert COPII from the secretory pathway to the autophagic pathway ar… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 54 publications
0
26
0
Order By: Relevance
“…However, a recent study demonstrated that the Sec23 paralogs can differ in functions due to posttranslational modifications (Jeong et al, ). There is growing evidence that COPII vesicles also promote autophagosome biogenesis by providing membranes, a process critically guided by Sec23B (Jeong et al, ). Under non‐autophagic conditions, Sec23B, but not Sec23A, is targeted by the F‐box protein FBXW5 for proteasomal degradation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a recent study demonstrated that the Sec23 paralogs can differ in functions due to posttranslational modifications (Jeong et al, ). There is growing evidence that COPII vesicles also promote autophagosome biogenesis by providing membranes, a process critically guided by Sec23B (Jeong et al, ). Under non‐autophagic conditions, Sec23B, but not Sec23A, is targeted by the F‐box protein FBXW5 for proteasomal degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Upon induction of autophagy, the Unc‐51‐like kinase is activated, which phosphorylates Sec23B, thereby preventing the interaction of Sec23B with FBXW5 and, thus, inhibiting Sec23B destruction. Stabilized Sec23B then associates with Sec24, thereby supporting COPII‐mediated autophagosome formation (Jeong et al, ). HBV and even the sole expression of its S protein had been shown to induce autophagy (Doring, Zeyen, Bartusch, & Prange, ; J. Li et al, ; Sir et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…When modified on sites within the trunk and β‐barrel domains of Sec23A (S207, S312 and T405), its interaction with Sec31A is dramatically reduced, suggesting that ULK1 activation impedes full COPII coat assembly required for secretory protein export from the ER, and shifts its function toward the biogenesis of donor membranes needed for autophagosome formation . ULK1 has also been shown to phosphorylate Sec23B within the trunk domain (S186) (Figure ), but in this case, phosphorylation disrupts an interaction with the F‐box protein FBXW5, which normally targets Sec23B for proteasome‐mediated degradation . In addition to stabilizing Sec23B, phosphorylation of Sec23B by ULK1 inhibits its binding to Sec24C and Sec24D, but not Sec24A or Sec24B, and allows for redistribution of Sec23B to ERGIC membranes to fuel autophagosome biogenesis .…”
Section: Regulation Of Copii Carrier Formation and Transport Mediatedmentioning
confidence: 99%
“…ULK1 has also been shown to phosphorylate Sec23B within the trunk domain (S186) (Figure ), but in this case, phosphorylation disrupts an interaction with the F‐box protein FBXW5, which normally targets Sec23B for proteasome‐mediated degradation . In addition to stabilizing Sec23B, phosphorylation of Sec23B by ULK1 inhibits its binding to Sec24C and Sec24D, but not Sec24A or Sec24B, and allows for redistribution of Sec23B to ERGIC membranes to fuel autophagosome biogenesis . At a mechanistic level, it remains unclear how phosphorylation of Sec23B would influence Sec24 binding in an isoform‐specific manner, but impaired association with Sec24C and Sec24D would likely reduce overall secretory protein efflux from the ER.…”
Section: Regulation Of Copii Carrier Formation and Transport Mediatedmentioning
confidence: 99%
“…Even less is known about how phagophore expansion is achieved and many cellular membranes have been suggested to act as lipid donors for this process [ 35 ]. Recently also COPII vesicles have been implicated as a potential membrane source for autophagosomes but their contribution to autophagosome formation remains to be investigated [ 36 , 37 , 38 , 39 ]. Recent studies demonstrating the ability of yeast Atg2 and mammalian ATG2A to tether high curvature vesicles and mediate lipid transfer between such vesicles shed light on a potential function of phagophore–ER contact sites [ 27 , 40 , 41 ].…”
Section: Phagophore Nucleation and Expansionmentioning
confidence: 99%